Novel Symbiotic Association Between Euwallacea Ambrosia Beetle and Fusarium Fungus on Fig Trees in Japan - Jiang, Zi-Ru; Masuya, Hayato; Kajimura, Hisashi (Frontiers in Microbiology, 2021)
Ficus carica plantations in Japan were first reported to be infested by an ambrosia beetle species, identified as Euwallacea interjectus in 1996. The purpose of this study was to determine the symbiotic fungi of female adults of E. interjectus emerging from F. carica trees infected with fig wilt disease. Dispersal adults (51 females) of E. interjectus, which were collected from logs of an infested fig tree in Hiroshima Prefecture, Western Japan, were separated into the three respective body parts (head, thorax, and abdomen) and used for the fungal isolation. Isolated fungi were identified based on the morphological characteristics and DNA sequence data. Over 13 species of associated fungi were detected, of which a specific fungus, Fusarium kuroshium, was dominant in female head (including oral mycangia). The plant pathogenic fungus of fig wilt disease, Ceratocystis ficicola, was not observed within any body parts of E. interjectus. We further discussed the relationship among E. interjectus and its associated fungi in fig tree.